Respostas

2014-08-27T10:01:10-03:00
A) usando adição de equações: x + 12y = 14 ... x = 14 - 12y
    substituindo  x na 1a.:  2( 14- 12y) + 5y = 9 ..... 28 - 24y + 5y = 9.......            -19y= -19...... y= 1
    substituindo y na 2a. : -x + 7 (1) = 5........ x= 2

b) x= -3 e y= 2
 
 c) x= 4 e y= 0                                                            
2014-08-27T10:13:16-03:00
A) usando adição de equações: x + 12y = 14 ... x = 14 - 12y
    substituindo  x na 1a.:  2( 14- 12y) + 5y = 9 ..... 28 - 24y + 5y = 9.......            -19y= -19...... y= 1
    substituindo y na 2 a. : -x + 7 (1) = 5. x= 2

b) x= -3 e y= 2
 
 c) x= 4 e y= 0